Anion conducting polymers based on ether linked polybenzimidazole (PBI-OO) - Henkensmeier, Dirk; Cho, Hyeongrae; Brela, Mateusz; Michalak, Artur; Dyck, Alexander; Germer, Wiebke; Ngoc My Hanh Duong; Jang, Jong Hyun; Kim, Hyoung-Juhn; Nam, SukWoo; Lim, Tae-Hoon (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Anion conducting polymers are potentially interesting for fuel cells, electrochemical pumps, and dye sensitized solar cells. Ether-containing polybenzimidazoles (PBI-OO and PBI-OPO) were synthesized and turned into anion conducting polymers by methylation. The thermal stability was shown to depend on the polymer structure and degree of methylation (dom). Tensile strength and modulus decrease between 50% and 75% dom, but stay constant or slightly increase over 75% dom again. At 65 degrees C, hydroxide, iodide, chloride, carbonate and bicarbonate conductivities of 0.1, 0.6, 19, 20, 31 mS/cm were obtained, respectively. The low hydroxide conductivity is due to the formation of a C-O bond in position 2 of the imidazolium, which reduces the number of free ions and is known to lead to imidazolium ring opening and further degradation steps. The effect of introduction of phenoxy groups into the main chain on the charge distribution, especially on position 2 and the methyl groups (positive charge on the methyl groups decreases the thermal stability), as well as on the ion bonding was thoroughly investigated by DFT calculations and correlated with experimental data. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: FOCK-SLATER CALCULATIONS; EXCHANGE MEMBRANES; ELECTROLYTE; APPROXIMATION; STABILITY; ENERGY